Research Competence Of Pupils As The Component Of Content Of Education - Kalibek Ybyraimzhanov, Gulden Yespolova,; Mussabekova, Gulvira (Opción, 2019)
The aim of the study is to investigate the research competence of pupils of primary classes as the component of the content of the updated education in Kazakhstan via comparative qualitative research methods. As a result, there are educational areas with high concentration of meta-subject content of education. In conclusion, one of the most important components of the content of the updated Kazakhstan education and means of implementing the chosen content in modern conditions is the research competence of pupils of primary classes.